PENGEMBANGAN DAN PENERAPAN MANAJEMEN PENGETAHUAN SEBAGAI STRATEGI PENDUKUNG KEGIATAN MEDIS NON-BEDAH (STUDI KASUS KLINIK PETUKANGAN MEDICAL CENTER) - Randy Andy; Dedy Sugiarto; Dorina Hetharia (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
On a new core competency-based industries, mutual information is the main asset in thecompetitive value to the business processes of an industry. The medical industry uses theinformation as a critical factor in every aspect of perform a clinic or hospital management. Theinformation of knowledge should been packaged in a process that is known as knowledgemanagement. Bennefit knowledge management in the medical industry is to improve the quality ofthe medical officer. It aims to minimize the malpractice cases occurrence that often occurs due tolack of knowledge between medical officer. The lack of knowledge often occurs because of gap ofknowledge between the members of the medical officer. Application of knowledge managementsystems that really serves transfer of knowledge from senior medical officer for a new medicalofficer. Failure of any expert (senior medical officer) in making decisions at the time of medicaltreatment can also be minimized by the knowledge management system.